Plants Metabolites: Possibility of Natural Therapeutics Against the COVID-19 Pandemic - Bhuiyan, Farhana Rumzum; Howlader, Sabbir; Raihan, Topu; Hasan, Mahmudul (Frontiers in Medicine, 2020)
COVID-19, a disease induced by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) has already shown a state of true pandemic circumstances in the present world. Though extensive research works are being reported in recent days for the development of effective therapeutics against this global health crisis, still, there is no approved therapy against the SARS-CoV-2. In the present study, plant synthesized secondary metabolites (PSMs) have been prioritized to make a review focusing on the efficacy of plant originated therapeutics for the treatment of COVID-19. Plant metabolites exhibit as a source of countless medicinal compounds while the diversity of multidimensional chemical structures has made them superior to treat serious diseases. Those have already been reported as promising alternative medicines and lead compounds for drug repurposing and discovery. The versatility of secondary metabolites may provide novel antibiotics to tackle MDR (Multi-Drug Resistant) microbes too. This review attempted to find out plant metabolites having therapeutic potentials to treat a wide range of viral pathogens. The study includes the search of remedies belonging plant families, susceptible viral candidates, antiviral assay, and the mode of therapeutic action; and this attempt made a collection of enormous natural therapeutics that might be suggested for the treatment of COVID-19. About 219 plants from 83 families were found having antiviral activity. Among them, 149 plants from 71 families were screened for the identification of the major plant secondary metabolites (PSMs) that might be effective at this pandemic situation. Our investigation revealed that the proposed plant metabolites can serve as potential anti- SARS-CoV-2 lead molecules for further optimization and drug development process to combat COVID-19 and future pandemics caused by viruses. This review will stimulate further analysis by the scientific community and boost antiviral plant-based research followed by novel drug designing.